CRITICAL THINKING AS A TOOL FOR UNMASKING THE IRRATIONAL CHARACTER OF THE ESTABLISHED ORDER - Omenukor, Donald Uchenna (African Journal of Social and Behavioural Sciences, 2024)
This paper explored the issue of critical thinking as a tool for unmasking the irrational character of the established order. The core purpose of every human society is the quest for wellbeing and happiness. However, the established order in society embodies numerous ills that keep the human being enchained even in the face of the professed freedom. These hidden ills that characterise the social and political order can also be unravelled by negative thinking which is critical thinking. Negative thinking which is critical thinking is the kind of thinking that is able to open up the repressive aspects that are hidden in the “progress” and “success” that are often celebrated by the society. The paper, drawing from content analysis, concludes that negative thinking as critical thinking could lead to the unbundling of true human freedom which will consist in true happiness for the person of contemporary society.